BRAINSTORMING IN THE CLASS - DOMISCHOVA, Ivona (Trends in education, 2010)
The contribution describes the teaching method called brainstorming, its principles and its general use in the class at elementary schools in the Czech Republic. It specifies its positive effect on pupils and describes some negative aspects of this method. This article evaluates its motivational and activation aspect.
Keywords: brainstorming; group; teaching method; ideas; creativity; lessons; positive aspects; negative aspects; self-assertion; motivation.